Le timbre de la complainte de Fualdès : « l’air de toutes les complaintes » - Sophie-Anne Leterrier (Criminocorpus)
The Fualdès Affair is one of the most famous bloody events of the 19th century, and the complaint relating to it has undoubtedly benefited from this notoriety, to such an extent that the air on which it was written has become "the air of all complaints". This air provides a kind of school case. It shows that the meaning of an aria depends more on its uses than on its objective characteristics (structure, melody, rhythm...). In songs, the choice of an aria is based on its ability to imply implicit content, thus transported from one song to another. This introduces a kind of intertextuality before the letter. The previous uses of the air predetermine him, and its posterity owes much to its parodies. With the Complaint of Fualdès, a funeral and military air (the air of the Marshal of Saxony), charged with political meaning by its uses during the Revolution, becomes successively suitable to carry the account of other criminal cases, then turns to burlesque, as the Case enters into legend.